Two Forms of Social Inequality in Students' Socio-Emotional Skills: Do the Levels of Big Five Personality Traits and Their Associations With Academic Achievement Depend on Parental Socioeconomic Status? - Lechner, Clemens M.; Bender, Jens; Brandt, Naemi D.; Rammstedt, Beatrice (Frontiers in Psychology, 2021)
Some researchers and policymakers advocate a stronger focus on fostering socio-emotional skills in the hope of helping students to succeed academically, especially those who are socially disadvantaged. Others have cautioned that this might increase, rather than reduce, social inequality because personality traits conducive to achievement are themselves unevenly distributed in disfavor of socially disadvantaged students. Our paper contributes to this debate. Analyzing representative, large-scale data on 9,300 ninth graders from the German National Educational Panel Study (NEPS) and using the Big Five personality traits as a measure of socio-emotional skills, we cast light on two related yet distinct aspects of social inequality in socio-emotional skills: First, do levels of personality traits conducive to achievement vary as a function of students' parental socioeconomic status (pSES)? Second, do the returns to personality traits in terms of trait–achievement relations vary as function of pSES? Results showed that differences in Big Five traits between students with different pSES were small (0.04 ≤ |r| ≤ 0.09), especially when compared with pSES-related differences in cognitive skills (fluid intelligence) and sex-related differences in personality. The returns to Conscientiousness—the personality trait most relevant to achievement—in terms of its relations to academic achievement were higher in higher- vs. lower-SES students. Trait–achievement relations did not vary as a function of pSES for the other Big Five traits. Overall, both types of inequality were limited in magnitude. We discuss the implications of these findings for policy and practice and delineate directions for further research.